Pemenuhan Hak Perempuan dan Anak Korban Tindak Pidana Perdagangan Orang Terhadap Pemulangan dan Reintegrasi Sosial di Provinsi Kalimantan Barat - Penny Naluria Utami (Badan Strategi Kebijakan Hukum, 2015)
Crime of Trafficking in Persons (TPPO), especially women and children is an act that is contrary to human dignity and a violation of human rights. The victim in this case was treated as merchandise that is bought, sold, transported and resold and deprived of their fundamental rights at risk even in death. Aims to determine the policies of local governments in the safe return of service in accordance with the needs of victims of crime of trafficking in women and children and the monitoring mechanism for victims who have been repatriated back so as not to become a victim. Necessary data consist of primary data and secondary data and the approach used is qualitative research and observation of participation that will be more talk is an informant, the researcher merely listened. Social Service is the agency responsible for handling the process of repatriation and social reintegration. Exit repatriation costs borne by the Ministry of Social region, while repatriation in the province use budget funds Provincial Social Service, in addition to the IOM also assists in the process of repatriation if there is demand. West Kalimantan Regional Police sometimes do return if the victim is domiciled in the province of West Kalimantan. Social reintegration has not run at all so monitoring of the victims who received services what is already independent and empowered. Processes are carried out only to the extent repatriation and social reahabilitasi. To do social reintegration handed over to the local government where the victims originate, which should be done jointly by the government and the government of West Kalimantan region of origin of victims to know the progress of the victim to have his life back either.